Expression, purification and X‐ray crystallographic analysis of the Helicobacter pylori blood group antigen‐binding adhesin BabA. Issue 12 (1st December 2014) - Subedi, Suresh; Moonens, Kristof; Romão, Ema; Lo, Alvin; Vandenbussche, Guy; Bugaytsova, Jeanna; Muyldermans, Serge; Borén, Thomas; Remaut, Han
<x xml:space="preserve">Abstract</x> Helicobacter pylori is a human pathogen that colonizes about 50% of the world's population, causing chronic gastritis, duodenal ulcers and even gastric cancer. A steady emergence of multiple antibiotic resistant strains poses an important public health threat and there is an urgent requirement for alternative therapeutics. The blood group antigen‐binding adhesin BabA mediates the intimate attachment to the host mucosa and forms a major candidate for novel vaccine and drug development. Here, the recombinant expression and crystallization of a soluble BabA truncation (BabA25–460) corresponding to the predicted extracellular adhesin domain of the protein are reported. X‐ray diffraction data for nanobody‐stabilized BabA25–460 were collected to 2.25 Å resolution from a crystal that belonged to space group P21, with unit‐cell parameters a = 50.96, b = 131.41, c = 123.40 Å, α = 90.0, β = 94.8, γ = 90.0°, and which was predicted to contain two BabA25–460–nanobody complexes per asymmetric unit.